Synergy between cilofungin and amphotericin B in a murine model of candidiasis. - Hanson, L H (1991)
The efficacies of cilofungin and amphotericin B separately and together in mice with disseminated candidiasis were studied. Male CD-1 mice (age, 5 weeks) were infected intravenously with 3 X 10(5) CFU of Candida albicans. At 4 days postinfection, intraperitoneal therapy was initiated and was continued for 14 days. Therapy groups included those given cilofungin at 6.25 or 62.5 mg/kg/day (given twice daily), amphotericin B at 0.625 mg/kg/day (given once daily), cilofungin at 6.25 mg/kg/day plus amphotericin B, and cilofungin at 62.5 mg/kg/day plus amphotericin B. Mice were observed through 30 days postinfection. All infected untreated mice died of infection between days 6 and 18. Eighty-five percent of mice receiving cilofungin at 6.25 mg/kg/day died between days 13 and 30. All other mice survived. Quantitative determination of the number of CFU of C. albicans in the spleens and kidneys of all survivors revealed that mice that had received both drugs had lower residual burdens of C. albicans. All mice treated with cilofungin at 62.5 mg/kg/day plus amphotericin B had sterile spleens, whereas 42 to 58% of mice given cilofungin or amphotericin B monotherapy had sterile spleens. All kidneys were infected in mice which had received cilofungin at 62.5 mg/kg/day or amphotericin B. Neither organ was infected in 17% of each group receiving combination therapy with cilofungin and amphotericin B. The number of CFU in the kidneys of mice treated with cilofungin at 62.5 mg/kg/day plus amphotericin B was lower than those cultured from mice treated with cilofungin at 62.5 mg/kg/day (P less than 0.001, Mann-Whitney) or amhotericin B (P less than 0.05). Modest synergy was noted in inhibition of the C. albicans isolate in vitro. Pharmacokinetic studies showed elevated levels of cilofungin but not amphotericin B in sera of mice treated with combined therapy compared with those in mice given monotherapy. No overt toxicity was evident with any regimen. The mechanism of increased efficacy may be altered cilofungin distribution, excretion, or metabolism; antifungal synergy; or both. These results indicate that concurrent cilofungin-amphotericin B therapy has synergistic or additive efficacy in vivo.